Chelas Zone J revisited: Urban morphology and change in a recovering neighbourhood - Borges, J. C.; Marat-Mendes, T.; Lopes, S. S. (5th ISUFitaly International Conference. Urban Substrata & City Regeneration. Morphological legacies and design tools, 2020)
Among new council housing areas from 1960s Lisbon is the Chelas Valley, by then overwhelmingly agrarian. Although an integral urbanization plan - the Plano de Urbanização de Chelas (PUC) – was prepared until 1964, the area was divided into six zones, urbanized in different periods, with great deviances from the original plan. Upon construction, Chelas was challenged by social problems. One of the zones, Zone J, has been particularly associated with this negative image. The architectural designs by Tomás Taveira and Victor Consiglieri introduced changes to the urban plan by Francisco Silva Dias and José Lobo de Carvalho. After construction, several municipal initiatives tried to improve living conditions in Zone J, ranging from façade changes to demolitions. All along, it has been accepted that the urban form of Zone J was a determinant factor of its failure as a habitat. Here, we revisit the original Zone J Plan. How was it implemented, and how has it changed since? What has been the input of the residents in the territory they inhabit? Can it contribute to make Lisbon a more sustainable city? This presentation aims to answer these questions while trying to identify parallels with other urban areas in a crisis that share morphological characteristics with Chelas Zone J.